2019
DOI: 10.3991/ijet.v14i23.10890
|View full text |Cite
|
Sign up to set email alerts
|

The Optimum Equilibrium when Using Experiments in Teaching – Where Virtual and Real Labs Stand in Science and Engineering Teaching Practice

Abstract: The present study compares the relative merits of virtual and real educational laboratories in science and engineering education, in terms of their educational effectiveness and if they were the most appropriate for learning. The age of the students was also investigates as a possible factor affecting the outcome. The authors of the present paper started by identifying 67 recent and mutually compatible research papers (articles, doctoral theses, and reviews) and reviewed their content performing a meta-study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…It should be taken into account that, in our study, age variations are small (the standard deviation for students' age is 2.2 years). Thus, the conclusions of previous studies (e.g., Tsichouridis et al, 2019) comparing different age levels (children vs. adolescents vs. adults) are not useful in order to interpret this age effect since the participants in our study are all at the same educational level.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…It should be taken into account that, in our study, age variations are small (the standard deviation for students' age is 2.2 years). Thus, the conclusions of previous studies (e.g., Tsichouridis et al, 2019) comparing different age levels (children vs. adolescents vs. adults) are not useful in order to interpret this age effect since the participants in our study are all at the same educational level.…”
Section: Discussionmentioning
confidence: 84%
“…One possible explanation for this lack of effect, according to the embodied cognition theory, is that the students in the virtual condition had, by past experiences, internalized the relevant perceptual knowledge that the structural kit would have given them. We must keep in mind that the majority of studies wherein a physical-virtual effect was found were the studies with young children (Lazonder & Ehrenhard, 2014;Tsichouridis et al, 2019;Zacharia et al, 2012), while in our study, the participants were university-level adults. Adults, unlike children, would have probably embodied the relevant perceptual knowledge from prior physical experiences (De Jong et al, 2013), in which case the presence of touch sensory feedback is no longer a necessary condition for improved understanding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consider, for instance, a simple in vivo demonstration of an action potential. The standard setup for this type of demonstration comprises several items, such as micromanipulator, microscope, stimulator, oscilloscope, amplifier, and data acquisition software, whose total cost is around US $ Although simulators have a demonstrated utility as a teaching tool in biology [15][16][17], many educators believe that they cannot replace the vivid, active and holistic experience of laboratory demonstrations (NRC 2006, NSTA, 2007.…”
Section: Highlights  Action Potential (Ap) In Earthwormmentioning
confidence: 99%
“…Therefore, the present pilot study focuses on examining a) if there is a significant improvement in the procedural knowledge of senior high school students after being subjected to an inquiry-based Teaching Learning Sequence (TLS) utilizing an open virtual laboratory environment in AC electric circuits, in which experimental procedures are explicitly taught and b) if there is a correlation between procedural and cognitive knowledge development after the implementation of this TLS. Answering these questions may help teachers design instruction more efficiently in order to assist students in secondary education in exploring physical phenomena by themselves in a laboratory environment, perceive them in their own personal way and acquire deeper understanding and longer retention of knowledge [9].…”
Section: Introductionmentioning
confidence: 99%